A Just Target of Health Social Insurance Assistance Receipients - Hikmawati, Eny (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research means to know the just target of social health insurance assistance receipients. The just target is urgent so that social insurance is effective. The research is conducted in Purworejo Regency with qualitative-descriptive method. Data are gathered through interview, observation, with informants of social insurance participants program who get PBI-JKN and Jamkesda, and documentary analysis related to social health insurance. The result concludes that social health insurance in Purworejo Regency has been done to the right targets. They are poor community comply with the indicator, reached through PBI-JKN with local central government budget, and poor group through local health insurance (Jamkesda) budget. The participation in local social health insurance refers to validation of PPLS 2011 so that does not fit with current condition. It needs newly data verification 2014-2015 for social assistance and social insurance 2015 through the Ministry of Social Affairs, through Central Data and Information in coordination with BPS. PPLS validation is conducted every six months by Directorate Social Protection and Insurance in coordination with TNP2K so that the information gets the right targets and benefit as social security network.